How different of the rhizospheric and endophytic microbial compositions in watermelons with different fruit shapes. - Jian Xiao; Jinyan Huang; Kezhuo Xiao; Guifen Li; Shangdong Yang; Yi He (PLoS ONE)
Fruit shape is an important character of watermelon. And the compositions of rhizospheric and endophytic microorganisms of watermelon with different fruit shape also remains unclear. To elucidate the biological mechanism of watermelon fruit shape formations, the rhizospheric and endophytic microbial community compositions between oval (OW) and circular watermelons (CW) were analyzed. The results showed that except of the rhizospheric bacterial richness (P < 0.05), the rhizospheric and endophytic microbial (bacterial and fungal) diversity were not statistically significant between OW and CW (P > 0.05). However, the endophytic microbial (bacterial and fungal) compositions were significantly different. Firstly, Bacillus, Rhodanobacter, Cupriavidus, Luteimonas, and Devosia were the unique soil dominant bacterial genera in rhizospheres of circular watermelon (CW); In contrast, Nocardioides, Ensifer, and Saccharomonospora were the special soil dominant bacterial genera in rhizospheres of oval watermelons (OW); Meanwhile, Cephalotrichum, Neocosmospora, Phialosimplex, and Papulaspora were the unique soil dominant fungal genera in rhizospheres of circular watermelon (CW); By contrast, Acremonium, Cladosporium, Cryptococcus_f__Tremellaceae, Sodiomyces, Microascus, Conocybe, Sporidiobolus, and Acremonium were the unique soil dominant fungal genera in rhizospheres of oval watermelons (OW). Additionally, Lechevalieria, Pseudorhodoferax, Pseudomonas, Massilia, Flavobacterium, Aeromicrobium, Stenotrophomonas, Pseudonocardia, Novosphingobium, Melittangium, and Herpetosiphon were the unique dominant endophytic bacterial genera in stems of CW; In contrast, Falsirhodobacter, Kocuria, and Kineosporia were the special dominant endophytic genera in stems of OW; Moreover, Lectera and Fusarium were the unique dominant endophytic fungal genera in stems of CW; By contrast, Cercospora only was the special dominant endophytic fungal genus in stems of OW. All above results suggested that watermelons with different fruit shapes exactly recruited various microorganisms in rhizospheres and stems. Meanwhile, the enrichments of the different rhizosphric and endophytic microorganisms could be speculated in relating to watermelon fruit shapes formation.